Abuse of authority of the chairman of the general election commission in the election process of the regent and deputy regent of Sabu Raijua - Filmon Mikson Polin (Trigin Publisher, 2022)
esearch with the title Abuse of Authority of the Chairman of the General Election Commission in the Election Process of the Regent and Deputy Regent of Sabu Raijua, the research problem is Why was there an abuse of authority by the Chairman of the General Election Commission of Sabu Raijua Regency? This research uses normative legal research, based on the results of research on Article 3 of Law Number 31 of 1999 in conjunction with Article 18 and Article 81 of Law Number 30 of 2014 in conjunction with Article 13 and Article 14 of Law Number 8 of 2015 and interviews with the chairman of Bawaslu Sabu Raijua, the conclusion is that the reason for the abuse by the general election commission in the election of regents and deputy regents of Sabu Raijua is due to juridical reasons, technical reasons and substance; because the Chairman of the General Election Commission of Sabu Raijua Regency did not carefully examine the requirements of the candidate pair for Regent and Deputy Regent of Sabu Raijua; dishonest in making decisions; for not complying with the warning letter of the Chairman of the General Election Supervisory Board of Sabu Raijua Regency.